Insight into Paphiopedilum x Dalatense Aver. (Orchidaceae) origin based on morphological and molecular markers - Thai Vinh, Tran; Nie Bing, H’ Yon; Kim Cong, Vu; Tham, Dang Thi; Phuong Linh, Ngo; Ngoc Trieu, Le; Duy, Nong Van (Vietnam Journal of Biotechnology, 2022)
Paphiopedilum callosum, Paphiopedilum villosum and Paphiopedilum ´ dalatense are endangered species and are currently listed as Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES, 2019) Appendix I species. Thus, the international trade for these naturally occurring species is forbidden. However, the in vitro propagated materials and their inter-species hybrids forced by breeders can be traded for commercial purposes. P. ´ dalatense is an endemic slipper orchid species of Vietnam with high aesthetic value. Currently, the natural reserves of this species have been greatly reduced by overexploitation. In this study, P. ´ dalatense was demonstrated to be the reversible hybrid species between P. callosum and P. villosum based on both morphological and molecular markers. P. ´ dalatense possesses intermediate morphological characteristics between P. callosum and P. villosum which could be recorded in leaf, in flower and its components such as lip, petal, and dorsal sepal. There were 23 sites in ITS1-5.8S rRNA-ITS2 region sequence of P. ´ dalatense which possess the nucleotide characteristic of both P. callosum and P. villosum. There were two out of three P. ´ dalatense investigated samples possessed partial matK gene which was identical to the corresponding sequence in P. villosum and the last sample possessed identical partial matK gene to P. callosum. Proving P. ´ dalatense to be the reversible hybrid species between P. callosum and P. villosum is the essentially scientific base for commercial breeding of P. ´ dalatense by artificial hybridization which contributes to avoid overexploiting the natural P. ´ dalatense resources.